Evaluation of discarded dates on the performance of Libyan local goats - Shrdh, I.A; Amaizik, S.A; Milad, I.S. (Al-Mukhtar Journal of Sciences, 2016)
This study was carried out in the experimental station of Animal Production Department, Faculty of Agriculture, Omar Al-Mukhtar University, El-Beida-Libya, during winter season 2013/2014 to investigate the effect of replacing 10 or 20% of the concentrate mixture with corresponding percentages of discarded dates on the performance of local growing male goats.Fifteen male goats (3-4 months old) with average body weight of 11.6 ± 0.47 kg were randomly allocated equally into 3 groups. A growth trial lasted 90 days preceded with 14 days of adaptation period. Digestibility trial was conducted with 9 animals (3/treatment) after the culmination of the growth trial. Blood samples were taken from the jugular vein for biochemical measurements.Chemical analysis indicated that, discarded dates contain 3.97%, 4.35%, 11.24%, 70.1% and 10.39% of CP, CFat, CFiber, NFE, and Ash, respectively.Total and daily gain were increased (P0.05) were observed in the final weights and consumption of concentrate feed. Total daily feed consumption was lower (P